Промислове садівництво Півдня України в рамках забезпечення продовольчої безпеки - Колокольчикова, Ірина Володимирівна; Колокольчикова, Ирина Владимировна; Kolokolchykova, Iryna (My University, 2019)
UK: У статті наведено результати дослідження рівня забезпечення продукцією садівництва населення України в рамках продовольчої безпеки. Розглянуто поняття «продовольча безпека» в її соціальному спрямуванні. Досліджено показники фонду споживання плодів, ягід і винограду в динаміці та виявлено тенденції змін. Проведено порівняльний аналіз норм споживання продукції галузі по природно–кліматичних зонах України. Розраховано показник достатності споживання фруктів у порівнянні з раціональними нормами. Встановлено причини недостатнього рівня споживання плодів в раціоні українців та подальші напрямки дій. EN: The results of the study provide levels of horticulture products to the population of Ukraine in the framework of food security. The concept of "food security» is considered. The indicators of the Fund of consumption of fruit in dynamics are investigated, tendencies of changes are revealed. The analysis of norms of consumption of production of branch on climatic zones of Ukraine is carried out. The indicator of sufficiency of consumption of fruit in comparison with rational norms is calculated. The reasons of insufficient level of consumption of fruits are defined. A new approach to the methodology of urban agglomeration planning in Ukraine.
Industrial gardening in the South of Ukraine within the framework of food security
Keywords: продовольча безпека; промислове садівництво; норми споживання; фонд споживання продукції; рівень достатності споживання; food security; industrial gardening; consumption norms; fund of consumption of products; level of sufficiency of consumption